Prevention and Treatment of Atherosclerosis Improving State-of-the-Art Management and Search for Novel Targets - von Eckardstein, Arnold; Binder, Christoph J. (Handbook of Experimental Pharmacology, 2022)
This open access book is supported by the European Atherosclerosis Society Association (EAS). This follow-up edition of the well-received Handbook volume 'Atherosclerosis: Diet and Drugs' reflects the state-of-the-art and most recent developments in atherosclerosis research. Outstanding international experts give a comprehensive overview of the field covering topics, such as improving the treatment focusing on established targets, novel drug developments addressing pre-defined targets, hypothesis-based and hypothesis-free approaches to unravel novel targets.